Balanced Scorecard Sektor Publik: Sebuah Pelajaran Berharga - Ali Tafriji Biswan; Wahyu Andika (InFestasi, 2020)
This research aims to understand and examine the application of the balanced scorecard as performance measurement tools. BSC is a performance measurement tool that combines financial and nonfinancial performance measurements. This research object is a public sector organization, the Directorate General of Financing and Risk Management (DJPPR) Ministry of Finance. The method used in this research is qualitative descriptive methods. The steps taken in this study are collection, classification, presentation, and tabulation of data obtained. Subsequently performed a systematic, accurate, and factual description regarding the facts of the object being inspected. This study uses DJPPR’s Performance Reports in 2018 and 2017. The results of the study indicate that the application of a balanced scorecard and DJPPR’s performance as a whole is good, which is shown by determining the perspective that has been aligned with the organization's strategy and its implementation encourages the achievement of performance targets.Penelitian ini bertujuan untuk memahami dan mengkaji penerapan balanced scorecard sebagai alat pengukuran kinerja. Balanced scorecard merupakan alat pengukuran kinerja yang mengkombinasikan pengukuran kinerja keuangan maupun kinerja nonkeuangan. Objek penelitian adalah organisasi sektor publik yaitu Direktorat Jenderal Pengelolaan Pembiayaan dan Risiko (DJPPR) Kementerian Keuangan. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Adapun langkah-langkah yang dilakukan dalam penelitian ini adalah pengumpulan, pengklasifikasian, penyajian, dan pengolahan data. Setelah itu melakukan deskripsi yang sistematis, akurat, dan faktual mengenai fakta-fakta dari peristiwa objek yang diteliti. Penelitian ini menggunakan Laporan Kinerja DJPPR tahun 2018 dan tahun 2017. Hasil penelitian menunjukkan bahwa penerapan balanced scorecard secara keseluruhan baik yang ditunjukkan dengan penentuan perspektif telah diselaraskan dengan strategi organisasi dan penerapannya mendorong pencapaian target kinerja.